Pengaruh Online Travel Agent Dan Online Review Terhadap Tingkat Hunian Kamar Di Hotel Grand Verona Samarinda - Kurniawan, Hendri; Aswan, Mukhamad Kholil (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to analyze the influence of Online Travel Agent (OTA) and online reviews on room occupancy rates at the Grand Verona Samarinda Hotel. The background of this study is based on the importance of digital transformation in the hospitality industry, especially in utilizing OTA platforms and customer reviews as marketing and reputation tools. The method used is quantitative with an explanatory approach through multiple linear regression analysis. A sample of 178 respondents was selected using a purposive sampling technique, and data was collected through a Likert scale questionnaire and secondary data from hotel management and OTA platforms. The results showed that both OTA (X₁) and online reviews (X₂) had a positive and significant effect on room occupancy rates (Y), with a coefficient of determination (R²) of 0.724. OTA has the most dominant influence with a beta value of 0.572, while online reviews show a beta of 0.319. In conclusion, digital distribution strategies through OTA and online reputation management are key factors in increasing room occupancy. It is recommended that hotels strengthen partnerships with OTA platforms and actively manage bold reviews to increase customer trust and sustainable room occupancy performance. Keywords: online travel agents, online reviews, room occupancy rates